DIGITALIZATION OF INVESTMENT AND CREATIVE ECONOMY: A NEW PATH TO INCLUSIVE GROWTH IN BERAU - Rosid, Tamam (Penelitian dan Pengembangan Ilmu, 2025)
Berau Regency faces challenges in optimizing investment potential and the creative economy as a driver of inclusive economic growth. This study analyzes digital transformation in the investment sector and the development of the creative economy as a sustainable economic development strategy. Using a descriptive-analytical approach, this study explores the implementation of the DPMPTSP digital platform, the adoption of digital investment technology, and the development of the creative economy sector including handicrafts, culinary, and art as the basis of the people's economy. The results of the analysis show that investment digitalization through the SIMOSI and TALI SIDA applications has increased the effectiveness of investment promotion, while the creative economy sector contributes significantly to job creation and empowerment of local communities. This research recommends the integration of more comprehensive digital platforms and the strengthening of the creative economy ecosystem through multi-stakeholder collaboration to realize inclusive and sustainable economic growth in Berau Regency.